Two-Weight Extrapolation on Lorentz Spaces - Wenming Li; Tingting Zhang; Limei Xue (Journal of Function Spaces)
We give several two-weight extrapolation theorems on Lorentz spaces which extend the results of Cruz-Uribe and Pérez (2000) and some applications for the singular integral operators, the potential type operators, and commutators.